Pengaruh Sisa Pakan dan Kotoran Ikan Nila, Ikan Lele dan Ikan Mas terhadap Pertumbuhan dan Hasil Tanaman Pakcoy Merah (Brassica rapa var. chinensis) pada Sistem Akuaponik - melasanty aditiya sagita; Anis Rosyidah; Abdul Basit (AGRONISMA, 2021)
The aquaponics system is an integrated system between aquaculture and hydroponics. Where fish farming waste is in the form of metabolic waste and leftover feed used as nutrients for plants. The plant used in this study was red pakcoy. The purpose of this study was to determine the effect of feed residues and manure of tilapia, catfish and carp in the aquaponics system on the growth and yield of red pakcoy (Brassica rapa var. Chinensis).This research was conducted in November 2020-February 2021. The research location was at the Experimental Garden of the Faculty of Agriculture, Islamic University of Malang. The research design used was a simple randomized block design (RAK) with 3 treatments, namely tilapia aquaponics (A1), catfish aquaponics (A2). ), and carp aquaponics (A3). The number of samples observed was 3 plants with each treatment repeated 7 times. So the total number of samples observed was 63 plants. This research uses the Deep Flow Technique (DFT) recirculation system.The results showed that the treatment of aisa feed and tilapia manure gave the best growth. The treatment of leftover feed and carp manure gave the best effect on the yield of red pakcoy plants, namely fresh weight (4.06 grams). The results of chlorophyll levels in the treatment of carp waste were the lowest, while for the vitamin C content there was no difference in the effect of the treatment of leftover feed and manure of tilapia, catfish and carp.